KEARIFAN LOKAL MASYARAKAT DALAM PENGELOLAAN AIR BERKELANJUTAN - Indah Fikriah (Pelantar Press, 2023)
The need for water for living things as life support is absolute, but in the last few decades, the existence of water as a resource has reached an alarming critical point. The community has local wisdom and local knowledge that has been well-proven in protecting and conserving nature. Local wisdom owned by the community can be applied in a sustainable water management system. The purpose of this scientific writing is to examine the forms of local wisdom in water management and to examine the relationship between local wisdom and sustainable water management, by emphasizing the sustainability aspects, namely, ecology, economy, and social. The method used in this scientific work is literature study. Local wisdom is in the form of knowledge, belief, understanding, and insight as well as customs that guide human behavior in life-related to the conditions of the region and indigenous communities. Local wisdom plays a role in efforts to maintain the three functions, namely ecological, social and economic aspects, to create harmony and balance that promises stability and sustainability of water management.